2015
DOI: 10.1016/j.applanim.2015.08.012
|View full text |Cite
|
Sign up to set email alerts
|

The effect of presenting forage in multi-layered haynets and at multiple sites on night time budgets of stabled horses

Abstract: Feline urine spraying inside the home is a common problem behaviour that owners seek advice for from veterinarians. Individual trials relating to a variety of interventions produce variable results, and to date, no consensus on the value of different treatments has emerged. This study therefore aimed to meta-analyse, current data from appropriate published clinical trials that evaluate treatments for feline urine spraying. Inclusion and exclusion criteria for study selection were predefined and methodological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 44 publications
6
39
0
Order By: Relevance
“…However, it has recently been reported that many stabled horses finish an evening meal before midnight [29] and this was observed here wherein the entire meal in the HG/LF group was consistently consumed within 4 h. This effectively resulted in a fast of approximately 10 h prior to the morning administration of the medication. However, it has recently been reported that many stabled horses finish an evening meal before midnight [29] and this was observed here wherein the entire meal in the HG/LF group was consistently consumed within 4 h. This effectively resulted in a fast of approximately 10 h prior to the morning administration of the medication.…”
Section: Discussionmentioning
confidence: 56%
“…However, it has recently been reported that many stabled horses finish an evening meal before midnight [29] and this was observed here wherein the entire meal in the HG/LF group was consistently consumed within 4 h. This effectively resulted in a fast of approximately 10 h prior to the morning administration of the medication. However, it has recently been reported that many stabled horses finish an evening meal before midnight [29] and this was observed here wherein the entire meal in the HG/LF group was consistently consumed within 4 h. This effectively resulted in a fast of approximately 10 h prior to the morning administration of the medication.…”
Section: Discussionmentioning
confidence: 56%
“…One potential weakness of the study is that the horses in the HG/LF diet were not specifically fasted. However, it has recently been reported that many stabled horses finish an evening meal before midnight (Ellis et al ., ), an effect observed by the authors of the present study wherein the entire meal in the HG/LF group was consistently consumed within 4 h. This effectively resulted in a fast of approximately 10 h prior to the morning administration of the medication. Further, the HG/LF diet was chosen as it is typical of the diet of Australian Thoroughbred racehorses (Southwood et al ., ; Richards et al ., ) and as such the authors propose that it represents the clinical scenario more accurately.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has recently been reported that many stabled horses finish an evening meal before midnight [113] and this was observed by the authors of the present study wherein the entire meal in the HG/LF group was consistently consumed within 4 hours. This effectively resulted in a fast of approximately 10 hours prior to the morning administration of the medication.…”
Section: Discussionsupporting
confidence: 50%